Regional Control of Chromosome Segregation in Pseudomonas aeruginosa. - Valentine Lagage; Frédéric Boccard; Isabelle Vallet-Gely (PLoS Genetics, 2016)
Chromosome segregation in bacteria occurs concomitantly with DNA replication, and the duplicated regions containing the replication origin oriC are generally the first to separate and migrate to their final specific location inside the cell. In numerous bacterial species, a three-component partition machinery called the ParABS system is crucial for chromosome segregation. This is the case in the gammaproteobacterium Pseudomonas aeruginosa, where impairing the ParABS system is very detrimental for growth, as it increases the generation time and leads to the formation of anucleate cells and to oriC mispositioning inside the cell. In this study, we investigate in vivo the ParABS system in P. aeruginosa. Using chromatin immuno-precipitation coupled with high throughput sequencing, we show that ParB binds to four parS site located within 15 kb of oriC in vivo, and that this binding promotes the formation of a high order nucleoprotein complex. We show that one parS site is enough to prevent anucleate cell formation, therefore for correct chromosome segregation. By displacing the parS site from its native position on the chromosome, we demonstrate that parS is the first chromosomal locus to be separated upon DNA replication, which indicates that it is the site of force exertion of the segregation process. We identify a region of approximatively 650 kb surrounding oriC in which the parS site must be positioned for chromosome segregation to proceed correctly, and we called it "competence zone" of the parS site. Mutant strains that have undergone specific genetic rearrangements allow us to propose that the distance between oriC and parS defines this "competence zone". Implications for the control of chromosome segregation in P. aeruginosa are discussed.